Where Will the British Go? and Why?* - Laroze-Prehn, D (WILEY, 2019)
Objective Immigration is a highly salient political issue. We examine the migration preferences of potential emigrants from the United Kingdom to determine whether the migration calculus is primarily economic or political. Methods A conjoint survey experiment was conducted with U.K. subjects drawn from the CESS, Nuffield College, Oxford University, student subject pool to identify causal drivers of emigration preferences. Results Logit estimation of emigration preferences indicates that economics and politics matters. Anti-immigrant rhetoric, "Trumpian policies," and the United States deter high-skilled U.K. potential emigrants; economic growth, education, and social benefits attract them. Politics and social benefits are more important for those on the political left, while economics and education weigh more heavily for those on the right. Conclusion What will attract the highly skilled migrants from a post-Brexit United Kingdom? Economics matters of course but for many of these potential emigrants politics is important-they are particularly sensitive to anti-immigrant rhetoric.